Pengaruh Metode Strafikasi Suhu Rendah, Krioprotektan Dan Kriopreservasi Terhadap Viabilitas Benih Rosela (Hibiscus sabdariffa L.) - Dede Suhendra,; Haryati Haryati; Luthfi A. M. Siregar (Jurnal Agroekoteknologi, 2014)
The objective of the research was to know effect of treatment low temperature, cryoprotectants,cryopreservation and it’s combination to seed viability of rosele. The research was conducted at theSeed Technology Laboratory, Agriculture Faculty, University of Sumatera Utara, Medan withheight ± 25 meters above sea level, in January to February 2014, using a randomized block designwith 5 level low temperature stratification, cryoprotectants and cryopreservation treatment as wellcombination and control. Parameters observed were moisture content seed (%), germination rate(day), germination normal (%), abnormal sprouts (%), seeds die (%), vigor index (%), wet weight ofsprouts (g), dry weight of sprouts (g). The results showed that rosele seed viability using liquidnitrogen significantly different than without giving liquid nitrogen, provision cryoprotectants andcooling rate -5°C temperature before it immersed in liquid nitrogen not were optimal.Keywords: seed rosele, low temperature stratification, cryoprotectans, cryopreservation